Acute esophageal necrosis after kidney transplantation: A case report. Issue 6 (12th February 2021) - Kim, Na Young; Lee, Yoo Jin; Cho, Kwang Bum; Jin, Kyubok; Lee, Ju Yup
Abstract: Rationale: Acute esophageal necrosis (AEN) is a rare syndrome with characteristic endoscopic and pathologic findings. It usually results from a combination of tissue hypoperfusion, impaired local defense barriers, and massive reflux of gastric contents. We report a case of AEN after a kidney transplant. Patient concerns: A 53-year-old man with hypertension and end-stage renal disease presented with abdominal pain and a single episode of hematemesis 14 days after kidney transplantation. Diagnosis: Upper endoscopy revealed circumferential black coloration in the mid to lower esophageal mucosa. Esophageal biopsy showed ulcer, and immunostains were negative for viral etiology. Interventions: Conservative management was done with total parenteral nutrition and proton pump inhibitor. Outcomes: The patient experienced no further episodes of hematemesis or abdominal pain and follow-up endoscopy showed remarkable changes from the black mucosa to a red friable mucosa with whitish exudates. Lessons: In the case, AEN occurred in the setting of normal blood pressure after major surgery despite the absence of preceding factors such as hypotension and infections. The possibility of AEN should be considered in patients with solid organ transplantation who present with abdominal pain, dysphagia, and hematemesis.